Analysis of the Factors Causing Bullying Behaviour of Class XI Students at MAN Singkawang - Kamaruddin Kamaruddin; Slamat Fitriyadi; Miranti Aulia Angel; Floria Kabora (International Journal of Multi Discipline Science, 2023)
This study aims to describe the factors that cause bullying behaviour of class XI students at MAN Singkawang. The research used is qualitative. The research subjects used were 13 people. The method used was the interview with sampling, the data source was purposive. Collection technique with triangulation. The results of this study indicated that factors causing bullying behaviour: (a) family factors were caused by a less harmonious family, incomplete (parents die or get divorced), communication between parents and children was not smooth, and unfair parenting; (b) the peer factor due to the excessive intensity of communication between peers allowed for the desire to bully at the instigation of their friends, so that they were considered to have full authority over their group; (c) the mass media factor, often excessive online gameplay and even more so the misuse of social media.